Education, Governance and Trade-Related Technology Diffusion in Latin America - Maurice Schiff; Yanling Wang (Institute for the Study of Labor (IZA), 2004)
This paper examines the impact on TFP of North-South trade-related technology diffusion in Latin America and the Caribbean (LAC). North-South R&D flows are constructed based on industry-specific R&D in the North, North-South trade patterns, and input-output relations in the South. The main findings are: (i) Education and governance raise the level of TFP directly; and (ii) education and governance also raise TFP through their interaction with foreign R&D in R&D-intensive industries. These results imply a) that potential virtuous growth cycles exist both in the level and in the growth of TFP, and b) that taking into account the interaction effects between trade, education and governance by reforming the policies simultaneously will have a greater impact on TFP.
Keywords: O54; O30; I20; F10; O38; 330; technology diffusion; trade; R&D intensity; education; governance; Latin America; Technologietransfer; Nord-Süd-Beziehungen; Produktivität; Bildungsniveau; Governance-Ansatz; Wirtschaftswachstum; Lateinamerika; Karibische Staaten